INTEGRATING THE ROLES OF STAKEHOLDERS IN PREVENTING THE HIV/AIDS TRANSMISSION IN EAST JAVA, INDONESIA - Koesbardiati, Toetik; Kinasih, Sri Endah; Mas'udah, Siti (Institute of Topical Disease Universitas Airlangga, 2017)
HIV/AIDS prevention is very important and absolutely necessary. HIV transmission is now entering a fairly alarming level, in which people with HIV/AIDS in certain subpopulations are emerging. Special steps and resources are thus needed to cope with the condition. There are some phenomena potentially encourage HIV transmissions, such as the increasingly common free sex, homosexuality, the use of unsafe and unsterile syringes in narcotics consumption, commercial sex workers and various high-risk sexual activities. One of the crucial concerns that arises when sending prostitutes back to their hometowns without any coordinated and holistic mechanism is that the prostitutes may cause the spreading of HIV/AIDS in their hometowns. The research objective is to provide the material (input) how the prostitutes themselves may cause the spreading of HIV/AIDS. The research employed descriptive method with a qualitative approach. The results showed that the implementation and the role division in the closure have been highly coordinated and holistic. The leading sector in the role division is the Social Welfare epartment of the Government in Surabaya. In terms of health aspects for the former prostitutes sent back to their hometowns, there has been no policies related to medical screening designed to identify the disease early. Screening is very important for early diagnosis during the post-closure phase. The screening mechanism is that the Provincial Health Department has to optimize the monitoring, coordination, cooperation, agreements and partnerships with stakeholders such as the Local Health Department and the National/Provincial/Distric AIDS Commission, NGOs that are concerned with the problems of HIV-AIDS, international organizations, professional organizations, community leaders, religious leaders and universities.